Dimerization of the guanine-adenine repeat strands of DNA - Vorlícková, M; Kejnovská, I; Kovanda, J; Kypr, J (Nucleic acids research, 1999)
Jovin and co-workers have demonstrated that DNA strands containing guanine-adenine repeats generate a parallel-stranded homoduplex. Here we propose that the homoduplex is a dimer of the ordered single strand discovered by Fresco and co-workers at acid pH. The Fresco single strand is shown here to be stabilized in aqueous ethanol where adenine is not protonated. Furthermore, we demonstrate that the strands dimerize at higher salt concentrations without significantly changing their conformation, so that the dimerization is non-cooperative. Hence, the Jovin homoduplex can form through a non-cooperative dimerization of two cooperatively melting single strands. The available data indicate that the guanines stabilize the Fresco single strand whereas the adenines cause dimerization owing to their known intercalation or clustering tendency. The guanine-adenine repeat dimer seems to be a DNA analog of the leucine zipper causing dimerization of proteins.
Keywords: denaturace nukleových kyselin; Nucleic Acid Conformation; Salts; soli; Guanine; Adenine; jednovláknová DNA; kyseliny; adenin; Dinucleotide Repeats; dinukleotidové repetice; Circular Dichroism; Nucleic Acid Denaturation; Acids; konformace nukleové kyseliny; dimerizace; Ethanol; ethanol; cirkulární dichroismus; vysoká teplota; DNA, Single-Stranded; Dimerization; guanin; Hot Temperature